Peran Kader Posyandu dalam Meningkatkan Kualitas Pelayanan Kesehatan Ibu Hamil di Desa Kupang, Kabupaten Sidoarjo - Adellia Eka Wandira; Lailul Mursyidah (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this study was to examine how Posyandu cadres contribute to improving maternal health services in Kupang Village, Sidoarjo Regency. The qualitative approach used included observation, interviews, and documentation with purposively selected informants. Soekanto's (2001) Role Theory, which encompasses active, passive, and participatory roles, served as the basis for this analysis. The results indicate that cadres have actively participated in data collection and mentoring pregnant women, but they have failed to master 25 basic skills, resulting in an ineffective rotation system. While participatory roles emerged in collaboration with the village government through the